Evaluation of the effects of automated distribution of salaries to the satisfaction level of cashiers in government offices in Iloilo City - Jolito, Joenifer S.; Quintilla, Ma. Liza D.; Serilo, Marlon C.; Tabares, Ma. Eden C.; Tribunal, Nancy Mae S. (1999)
The study delves into the implementation of the automated system to the satisfaction of government cashiers. The findings of this study could serve as the basis for subsequent executions of the said system and of mechanizing other transactions. The COA Regional office Memorandum Number VI-97002 urges all Regional Supervising Auditors, Provincial auditor, Unit Heads and Team Unit Supervisors/Leaders to avail the services of banks and financial institutions in disbursing the employees' salaries to reduce, if not to eliminate, untoward incidents such as robbery and questionable delays. The proposed remedial action, payroll-thru-bank scheme is founded from the fundamental principles governing financial transactions. The use of the proposed remedial action is mandatory except for those institutions not in the reach of the expanded network of banks. Instillation is encouraged within the year 1997 if such scheme is feasible. With reference to the COA Memorandum, the researchers would like to determine if the automation of salary disbursement have an effect on the job satisfaction level of government cashiers, founded in the hypothesis that the automation will decrease the level of satisfaction. The research will focus on the effect of the shift from manual payroll to payroll-thru-bank scheme on the intrinsic, extrinsic and social factors of job satisfaction. Extrinsic factors relate to outside condition that is apart from the job set by his working environment. Among such factor includes physical working condition, pay and compensation fringe benefits snd co-workers. Intrinsic factors refer to the mediate connection between the worker and the job such as opportunities provided by work. These factors are inner and subjective attitudes of the worker to the job. Social factors are attributed to the interaction of the worker to his fellow employee. Government offices in Iloilo City totaled to 99 and only 10 those listed offices are using ATM as system of payment. The automated offices provided the study with 15 respondents having only three (3) male respondent. The average length in service of the respondents as government employee is 5.73 years with 1.23 years of using the automated distribution. The treatment of co-workers is the primary factor in the job satisfaction of the respondents. It is followed by feeling of accomplishment and treatment of superior officers. In general, only the social and intrinsic factors significantly affect the satisfaction of the cashiers. Among the extrinsic factors, only the physical working condition improved that led to a corresponding increase in satisfaction process and this development improved the respondents' satisfaction. The automated process is highly favored by the respondent for it is effecient, effective and convenient. Due to these, most respondents agrees to the automation of their other tasks.
[Research Paper] (BA 200 - Business Research) -- Iloilo City : UPV-CM, March 29, 1999.